(untitled) (Research, Society and Development, 2021)
The late diagnosis of odontogenic cystic lesions is common due to their asymptomatic growth. Among the treatments proposed in the literature, currently the decompression or marsupialization is indicated to reduce the size of the cyst, for subsequent complete enucleation of the lesion. The use of image intensifier during the transoperative period is commonly performed for orientation and localization of foreign bodies, firearm projectiles or fractured needles, and is hardly reported in studies to aid in the treatment of odontogenic cysts. The present article aims to report a clinical case of a young patient diagnosed with odontogenic keratorcyst, who underwent marsupialization treatment and subsequent cyst enucleation. During the transoperative, it was difficult to locate the unerupted tooth associated with the lesion, due to the large displacement to the base of the mandible. Thus, the image intensifier was used to locate and remove the tooth. Transoperative complications are common, especially when dealing with extensive cystic lesions, due to the degree of difficulty. The use of techniques and equipment that provide benefits in facilitating and speeding up the surgical procedure leads to a reduction in patient morbidity. The use of image intensifier is feasible in unusual situations, both for the location of foreign bodies and teeth in atypical locations.